The Dispute Board as an Alternative Dispute Resolution Mechanism In Public -Private Partnership (PPP) Projects in Indonesia - Desliana Maharani Nur Fitri; Prita Amalia (Journal of Law, Politic and Humanities, 2026)
PPP is an instrument in the provision of infrastructure in Indonesia to close the state financing gap and increase private participation. However, the character of PPP as a risk-based long-term contract makes this project vulnerable to disputes originating from various aspects. Based on Presidential Regulation Number 38 of 2015, the settlement of PPP disputes is carried out in stages through consensus deliberation, mediation, and arbitration or court. These mechanisms are often considered less effective because they take a long time, are high in cost, and have the potential to disrupt the sustainability of projects and the certainty of public services. This study aims to analyze the potential for disputes in PPP projects in Indonesia and examine dispute boards as an alternative dispute resolution method that is effective and preventive. The research method used is normative juridical with legislative, conceptual, comparative, and case study approaches, through the analysis of the national legal framework and comparison of dispute board practices in the United States and Australia. The results of the study show that the dispute board functions as a dispute prevention mechanism through continuous monitoring of the project from the beginning of the contract. Although it is well known in the construction services sector, there is no specific dispute board arrangement in the PPP regime in Indonesia. Thus, this study emphasizes the urgency of strengthening dispute board regulations within the framework of PPP to increase legal certainty, maintain long-term contract stability, and create a conducive investment climate. Keywords: PPP, Dispute board, Dispute Resolution